Building Relationships to Improve International Marketing Branding of Blimbing Batik SMEs in Malang City - Ayu Agus Tya Ningsih; Ratnawati; Firina Lukitaningtias; Ni Wayan Suarniati; M. Taufiq Noor Rokhman; Muhammad Hazim Bin Mohd Azhar (Sahwahita: Community Engagement Journal, 2026)
This international community service program is a collaborative initiative between Wisnuwardhana University, Indonesia, and Universiti Malaya, Malaysia. This activity aims to strengthen the capacity of Blimbing Batik SMEs to face the challenges of globalization through an internationally oriented branding strategy. The main focus of the community service is building strategic relationships with business partners, the international community, and supporting institutions so that Blimbing Batik can penetrate the global market with a strong cultural identity. Implementation methods include intensive mentoring, digital branding training, developing a batik cultural narrative as a selling point, and facilitating international networking through workshops and business matching. This program also emphasizes the importance of cross-border collaboration in strengthening the competitiveness of MSMEs, with Universiti Malaya acting as an academic partner, opening access to international networks and providing a global marketing perspective. The expected outcomes of this activity are an increased ability of Batik Blimbing MSMEs to build international business relationships, the development of a branding strategy consistent with local cultural values, and the creation of sustainable export opportunities. Thus, this community service not only contributes to strengthening the local economy of Malang City but also serves as a model for cross-border academic collaboration in supporting MSMEs in entering the international market